Body posture evaluations in subjects with internal temporomandibular joint derangement - Munhoz, Wagner Cesar [UNESP]; Marques, Amélia Pasqual (W. S. Maney & Son Ltd, 2009)
The aim of this study was to verify possible relationships between global body posture and temporomandibular joint internal derangement (TMJ-id), by comparing 30 subjects presenting typical TMJ-id signs to 20 healthy subjects. Body posture was assessed using the analysis of muscle chains on several photographs. Results show a higher frequency of lifted shoulders (p=0.04) and of changes in the antero-internal hip chain (p=0.02) in the test group, but no further differences were found significant between the control and test groups. The test group was then divided into three subgroups according to the Helkimo index of temporomandibular disorder severity. Again, no significant differences were found between the subgroups. However, there was a trend noticed in the group with the most severe dysfunction, to present a forward head and shoulders posture. Results are discussed in light of previous studies using the same sample.